BIOTRANSFORMASI 3-SIANOPIRIDIN MENJADI NIKOTINAMIDA DENGAN SEL CORYNEBACTERIUM D5 SEBAGAI BIOKATALIS - Sunarko, Bambang; Sulistinah, Nunik (Teknologi Indonesia, 2011)
A number of microbes isolated from industrial effl uents were studied to characterise their capability to convert 3-cyanopiridine. Isolate D5, identifi ed as Corynebacterium D5, was able to hydrolise 3-cyanopridin to nicotinamide, nicotinic acid, and ammonia catalyzed by nitrile-hydratase and amidase. The activity of nitrile-hydratase and amidase of Corynebacterium D5 were 0.364 U nad 0.200 U, respectively. The optimum hydrolisis of 3-cyanopiridine were occurred at 25oC and pH 7.0. Corynebacterium D5 exhibited the best growth (0.43 g cells dry weight/liter), when 0.5% (v/v) acetonitrile and 20 mM 3-cyanopiridine were used as sources of carbon, energy, and nitrogen.